Pengembangan Website POLARAS (Politik ala Rasulullah) untuk Mengenalkan Keteladanan Politik Nabi Muhammad SAW di Sekolah Dasar - Nurhayati, Ella; Nuraeni, Tresna; Adrian, Karan Bagas; Aeni, Ani Nur (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The presence of internet network technology has become a new alternative in conveying information by connecting all existing computer devices so that information can be accessed more widely and without the time and place restrictions. Students are expected to be able to take part in comfortable learning and so educators are required to be professional and able to create creative learning. But the fact is that there are still few educators who use websites as learning media, especially PAI teachers. From the survey data, it was found that 62% of PAI teachers had never used the website as a learning medium. Therefore, this research is expected to help introduce the political example of the Prophet Muhammad to grade 5 elementary school students through the development of the POLARAS website (Politics Ala Rasulullah) which is used as a support to support interactive learning activities. The method used by researchers is the D&D method with a mixed methods research approach and then collaborated with a qualitative approach. The use of the POLARAS Website (Politics Ala Rasulullah) makes it easier for teachers to carry out learning in the classroom, students can also easily access the POLARAS Website (Politics Ala Rasulullah) to be able to study independently. Learning by using POLARAS Website media (Politics Ala Rasulullah) can increase learning motivation and create fun learning. This website has also met the needs and satisfaction of students in terms of accessibility, use, content, understanding, and a fun learning experience.